2020
DOI: 10.1002/rth2.12433
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen concentrate for bleeding in patients with congenital fibrinogen deficiency: Observational study of efficacy and safety for prophylaxis and treatment

Abstract: Background Congenital fibrinogen deficiency (CFD) is a rare bleeding disorder characterized by reduced levels (afibrinogenemia, hypofibrinogenemia) or dysfunctional fibrinogen (dysfibrinogenemia), for which fibrinogen supplementation is the mainstay treatment. Objectives To assess the efficacy and safety of human fibrinogen concentrate (FCH) in patients with CFD. Methods This was a multicenter, noninterventional, retrospective cohort study with a 12‐month prospective follow‐up period in the United States and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Lasky et al [52] reported the effectiveness of HFC with treating ≥97% of the bleeding events and perioperative hemostasis in ≥98.5% minor or major surgeries. The bleeding events in patients receiving HFC for routine prophylaxis were infrequent with median annualized bleeding rates of 1.4 and 1.3 for retrospective and prospective periods of the study, respectively.…”
Section: Available Evidence On Hfc Replacement In Cfdmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasky et al [52] reported the effectiveness of HFC with treating ≥97% of the bleeding events and perioperative hemostasis in ≥98.5% minor or major surgeries. The bleeding events in patients receiving HFC for routine prophylaxis were infrequent with median annualized bleeding rates of 1.4 and 1.3 for retrospective and prospective periods of the study, respectively.…”
Section: Available Evidence On Hfc Replacement In Cfdmentioning
confidence: 99%
“…In the FOR-MA-02 study, a single thrombotic event was reported in a patient, while allergic or hypersensitivity reactions were not observed [51]. Pallor, chills, cough, vomiting, headache, urticarial, erythematous rash [53], thrombosis [52], and anaphylactic reactions (hypotension, cyanosis, and abdominal and back pain) [53,56] have been reported.…”
Section: Safety Of Hfc In Cfdmentioning
confidence: 99%
“…Plasma-derived fibrinogen concentrate (FC) is the optimal option as it generally considered safer and easier to handle compared to fresh frozen plasma and cryoprecipitate (4). Infusion of FC for treatment or prevention has been helpful in patients with afibrinogenemia (5). However, a potential link between FC and thromboembolism events have been reported (6), although causality is often not established, and pharmacovigilance data suggest that this risk, if any, is low (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…4 Infusion of FC for treatment or prevention has been helpful in patients with afibrinogenemia. 5 However, a potential link between FC and thromboembolism events have been reported, 6 although causality is often not established, and pharmacovigilance data suggest that this risk, if any, is low. 7 8 To date pathogenesis of thrombosis in afibrinogenemia is only partially understood 9 and there are no reliable tools to identify which patients are at risk of thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Cryoprecipitate was originally developed as a therapy for treating congenital factor VIII deficiency in the 1950s [ 7 ], but later it was also applied in the cases of von Willebrand disease, hypofibrinogenemia, or fibrinogen replacement therapy in fibrinogen deficiency [ 6 ]. However, in the case of fibrinogen deficiencies, cryoprecipitate has been largely replaced by human fibrinogen concentrates due to safety reasons [ 8 ].…”
Section: Introductionmentioning
confidence: 99%